Additive value of transarterial embolization to systemic sirolimus treatment in kaposiform hemangioendothelioma. Issue 9 (3rd December 2020) - Brill, Richard; Uller, Wibke; Huf, Veronika; Müller‐Wille, René; Schmid, Irene; Pohl, Alexandra; Häberle, Beate; Perkowski, Sybille; Funke, Katrin; Till, Anne‐Marie; Lauten, Melchior; Neumann, Jacob; et al.
Abstract: Kaposiform hemangioendothelioma (KHE) is a rare vascular tumor in children, which can be accompanied by life‐threatening thrombocytopenia, referred to as Kasabach‐Merritt phenomenon (KMP). The mTOR inhibitor sirolimus is emerging as targeted therapy in KHE. As the sirolimus effect on KHE occurs only after several weeks, we aimed to evaluate whether additional transarterial embolization is of benefit for children with KHE and KMP. Seventeen patients with KHE and KMP acquired from 11 hospitals in Germany were retrospectively divided into two cohorts. Children being treated with adjunct transarterial embolization and systemic sirolimus, and those being treated with sirolimus without additional embolization. Bleeding grade as defined by WHO was determined for all patients. Response of the primary tumor at 6 and 12 months assessed by magnetic resonance imaging (MRI), time to response of KMP defined as thrombocyte increase >150 × 10 3 /μL, as well as rebound rates of both after cessation of sirolimus were compared. N = 8 patients had undergone additive embolization to systemic sirolimus therapy, sirolimus in this group was started after a mean of 6.5 ± 3 days following embolization. N = 9 patients were identified who had received sirolimus without additional embolization. Adjunct embolization induced a more rapid resolution of KMP within a median of 7 days vs 3 months; however, tumor response as well as rebound rates were similar between both groups. Additive embolization may be of value for a more rapid rescue of consumptive coagulopathy in children with KHE and KMP compared to systemic sirolimus only. Abstract : What's new? Kaposiform hemangioendothelioma (KHE) is a rare vascular tumor in children. Up to 70% of these patients also develop a life‐threatening, consumptive coagulopathy known as Kasabach‐Merritt Phenomenon (KMP). Sirolimus is proving to be an effective therapy for both KHE and KMP. However, it can take several weeks for sirolimus to have an effect. In this study, the authors found that initial treatment with embolization provides a rapid rescue from the symptoms of KMP. Image‐guided, transarterial embolization may thus provide a valuable adjunct to sirolimus therapy of KHE/HMP.